2018
DOI: 10.1016/j.jdent.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of 3 intraoral scanners and accuracy of conventional impressions: A novel in vivo analysis method

Abstract: Intraoral scanners can be used as a replacement for conventional impressions when restoring up to ten units without extended edentulous spans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(162 citation statements)
references
References 14 publications
8
146
1
7
Order By: Relevance
“…e best-fit algorithm of the analysis software was applied for comparison. Positive and negative discrepancies were shown by the software as in a coloured map [22]. e discrepancy values were calculated from RMS (Root Mean Square) values of 10 superimposition data of each scanner.…”
Section: Datasetsmentioning
confidence: 99%
“…e best-fit algorithm of the analysis software was applied for comparison. Positive and negative discrepancies were shown by the software as in a coloured map [22]. e discrepancy values were calculated from RMS (Root Mean Square) values of 10 superimposition data of each scanner.…”
Section: Datasetsmentioning
confidence: 99%
“…This is the reason why, in this study, the prepared models were designed for quadrants. The scanner used in the study has been shown to have a high accuracy for scans of quadrants . In this study, isthmus width rather than perimeter or volume of the cavity preparation was used.…”
Section: Discussionmentioning
confidence: 99%
“…The widely used Trios intra-oral scanning device uses advanced parallel confocal imaging. In principle, this device [43][44][45][46] captures sets of 2D images of the oral cavity and then combines them into a spatial model using optical sectioning technology [41] and geometrical modelling. STL data exported from the Trios intra-oral scanner into the Matlab and Comsol computational environments were used to construct and analyze digital models of the lower and upper dental arches.…”
Section: Scanning Technologies In Spatial Model Constructionmentioning
confidence: 99%